Murder at the Hotel Orient - Ranelli, Alessandra (Scout Press, 2026)
"In Vienna, city of spies, American Sterling Lockwood is the loyal concierge at the infamous Hotel Orient. After the double murder of her ex-girlfriend, a sex worker, and a tech mogul building an Austrian surveillance state, Sterling has to turn detective. But finding the truth will require breaking the Orient's sacred code of secrecy, while keeping a few secrets of her own. The police struggle when modern investigative technologyproves useless at the old-fashioned hotel. Because clients use aliases, pay cash, and stay mere hours, all suspects have vanished. Sterling agrees to assist alongside her best friend and colleague Fernando, if only to avoid arrest and the suspicion regarding her own movements that night. As enemies close in, she risks everything to solvea case haunted by the past in a city with a fetish for nostalgia"--